Human 4E-T represses translation of bound mRNAs and enhances microRNA-mediated silencing. - Kamenska, A.; Lu, W.T.; Kubacka, D.; Broomhead, H.; Minshall, N.; Bushell, M.; Standart, N. (Nucleic Acids Research, 2014)
A key player in translation initiation is eIF4E, the mRNA 5' cap-binding protein. 4E-Transporter (4E-T) is a recently characterized eIF4E-binding protein, which regulates specific mRNAs in several developmental model systems. Here, we first investigated the role of its enrichment in P-bodies and eIF4E-binding in translational regulation in mammalian cells. Identification of the conserved C-terminal sequences that target 4E-T to P-bodies was enabled by comparison of vertebrate proteins with homologues in Drosophila (Cup and CG32016) and Caenorhabditis elegans by sequence and cellular distribution. In tether function assays, 4E-T represses bound mRNA translation, in a manner independent of these localization sequences, or of endogenous P-bodies. Quantitative polymerase chain reaction and northern blot analysis verified that bound mRNA remained intact and polyadenylated. Ectopic 4E-T reduces translation globally in a manner dependent on eIF4E binding its consensus Y30X4L site. In contrast, tethered 4E-T continued to repress translation when eIF4E-binding was prevented by mutagenesis of YX4L, and modestly enhanced the decay of bound mRNA, compared with wild-type 4E-T, mediated by increased binding of CNOT1/7 deadenylase subunits. As depleting 4E-T from HeLa cells increased steady-state translation, in part due to relief of microRNA-mediated silencing, this work demonstrates the conserved yet unconventional mechanism of 4E-T silencing of particular subsets of mRNAs.